A review of sediment fingerprinting for erosion hotspot assessment in southern Africa. Issue 1 (5th January 2021) - Stander, M. H.; Le Roux, J. J.; Abd Elbasit, M. A. M.; Liu, G.
ABSTRACT: Sediment fingerprinting techniques are increasingly utilized across the globe to identify and quantify sources of sediment in catchments to assist adequate management and rehabilitation strategies. The technique generally includes classifying source groups, sampling sediment sources and sink zones, analysing tracers and applying statistical analyses to discriminate and quantify the contribution from sources. Although sediment fingerprinting has been used in southern African catchments, a contextual review of studies for the region does not exist. An overview is given of the basic methodological steps, including the tracers utilized in southern Africa, the history and main findings of the studies and recommendations for further research. There are many regions in southern Africa where this technique can still be implemented, especially erosion hotspots of Lesotho and Swaziland. Similar to regions elsewhere, the technique has not been standardized due to variability of erosion processes and causal factors in different environments. Several studies state that soil is the dominant erosion factor in South Africa, especially in catchments that consist of duplex and dispersive soils that are highly erodible. It is recommended that a tracer or set of tracers be found for these problem soils. Sediment fingerprinting has the potential to discriminate soils as potential sediment sources.